2013
DOI: 10.1007/s10029-013-1070-2
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling characteristics and biomechanical properties of a crosslinked versus a non-crosslinked porcine dermis scaffolds in a porcine model of ventral hernia repair

Abstract: Purpose The objective of this study was to evaluate the histologic remodeling profile and biomechanical properties of the porcine abdominal wall after repair with HDMI-crosslinked (Permacol®) or non-crosslinked (Strattice®) porcine dermis in a porcine model of ventral hernia repair. Methods Bilateral incisional hernias were created in Yucatan minipigs and repaired after 21 days. The repair site, including mesh and abdominal wall, was harvested after 1, 6, and 12 months and subjected to histologic analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 15 publications
2
45
0
4
Order By: Relevance
“…However, because cross-linked ECM bioscaffolds are unable to degrade, their persistence in situ typically leads to a foreign body reaction (Anderson et al 2008) with the formation of connective tissue encapsulation Cavallo et al 2015). Crosslinked ECM biomaterials have also been shown to elicit a proinflammatory macrophage phenotype, rather than the anti-inflammatory and pro-remodeling phenotype induced by the native ECM bioscaffold Keane et al 2012).…”
Section: Biologic Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because cross-linked ECM bioscaffolds are unable to degrade, their persistence in situ typically leads to a foreign body reaction (Anderson et al 2008) with the formation of connective tissue encapsulation Cavallo et al 2015). Crosslinked ECM biomaterials have also been shown to elicit a proinflammatory macrophage phenotype, rather than the anti-inflammatory and pro-remodeling phenotype induced by the native ECM bioscaffold Keane et al 2012).…”
Section: Biologic Scaffoldsmentioning
confidence: 99%
“…ECM degradation also appears necessary to drive the inflammatory response toward resolution, avoiding the presence of a chronic inflammatory scenario. ECM degradation products produced during tissue remodeling, called cryptic peptides (Anderson et al 2008;Agrawal et al 2011a,b;Daly et al 2012), together with the release of the GFs retained in the ECM (Hodde et al 2001;Rieder et al 2004;Badylak 2014;Cavallo et al 2015), are believed to be responsible for many aspects of ECM-mediated bioactivity. Cryptic peptides are either created or exposed after the proteolysis of ECM components such as collagen, laminin, and fibronectin and their bioactivity is not present in the parent molecule (Anderson et al 2008;Daly et al 2012).…”
Section: Mechanisms Of Ecm Bioscaffold Remodelingmentioning
confidence: 99%
“…Some authors have argued that modifying the extracellular structure of the collagenous matrix by crosslinking could prevent host cell penetration and neovascularization and thus impair the remodeling process [12]. Other authors [20] reported that HDMI collagen crosslinking of porcine dermis scaffolds reduced the early histological remodeling profile but did not significantly impact the tensile strength or stiffness of graft-tissue complexes in a porcine model of ventral hernia repair. Deeken et al [21] claim that this limitation of crosslinked meshes may be insignificant in the long term, reporting that although crosslinking differentiated biological meshes early on, at 1 year, histological features such as cell penetration and neovascularization were no longer affected.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cross-linked porcine meshes are more antigenic and, are thus, replaced by scar, whereas non-cross-linked meshes are less antigenic and are replaced by regenerate tissue. Regenerate tissue exhibits a greater degree of cellular infiltration, degradation, deposition of extracellular matrix, neovascularization, lower inflammatory cell response, and less scar encapsulation, whereas scar tissue has limited host cell and vessel infiltration, more fibrotic matrix, and aligned collagen deposition (40,95).…”
Section: Degradationmentioning
confidence: 99%